Method Development for Compression Testing of Synthetic Ballistic Gelatine - Clarke, Emma (Cranfield University, 2024)
Poster contribution to the Defence and Security Doctoral Symposium 2023
Keywords: Ballistic gelatine; Digital image correlation; Quasi-static; DSDS23; DSDS23 Poster